PENGARUH LATIHAN PLYOMETRIC STANDING JUMP TERHADAP PENINGKATAN VERTICAL JUMP PEMAIN BOLA VOLI TUNAS HARAPAN PONOROGO - Febri Herdion Alfio Ozon; Vera Septi Sistiasih (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2023)
The aim of this study is to determine the effect of plyometric standing jump training on the vertical jump ability of Tunas Harapan Ponorogo volleyball players. The population to be study is 45 people and a sample of 16 people. The sample is divide into 2 groups, namely the experimental group and the control group. The experimental group will be given plyometric standing jump training while the control group will not be given any treatment. The collection technique using is by tests and measurements. The measurement test instrument used in this study is the vertical jump test. The data analysis using is by using the t-test (Paired Sample Test). From the statistical analysis it can be seen that the value of Sig. (2 -tailed) is obtained by 0.000 so it is less than 0.05 (<0.05), so this means that the null hypothesis is rejected (H0 is rejected) and the first hypothesis is accepted (H1 is accepted). That way, it can be concluded that there is a significant effect of plyometric standing jump training on the vertical jump ability of the volleyball players at the Tunas Harapan Ponorogo club. From the results of the research that has been carried out, the researchers hope to provide benefits for volleyball coaches and sports teachers in implementing plyometric standing jump exercises to improve volleyball players' vertical jump abilities. This also helps volleyball athletes improve their ability to do vertical jump.